Pembuktian Efek Fisher di Indonesia dalam Kerangka Inflation Targeting: Aplikasi Model Dinamis (Januari 2003 – Mei 2008) - Maruto Umar Basuki; Teguh Santoso (EKO-REGIONAL, 2009)
Since any the promulgation of the new central bank law, Act No. 23 of 1999 concerning Bank Indonesia,  this law subsequently amended by Act No.3 of 2004, which removed goal independence from Bank Indonesia. Under New law, the Government determines the inflation target after consultations with Bank Indonesia. This study investigated relationship between interest rate and nominal inflation on the Inflation Targeting Framework and extent to which The Fisher Effect Fisher hold. The Fisher Effect is one of the oldest and simplest ways to model the relationship between interest rate and expected inflation. In strong version (full Fisher effect ), the nominal interest rate (in this study nominal interest  rate can be represented with SBI) responds one-for-one to change in expected inflation, whereas in the weak version the expected has positive and statistically significant. The validity of the Fisher effect has important implications for monetary policy and needs to be considered by Bank Indonesia. Few studies have been conducted in Indonesia to validate this important hypothesis. The anaysis uses monthly data, the data is  the 3 month of SBI rate and actual inflation from January 2003 to May 2008. The data analysis using dinamaic model, Autodistributed lag (ADL) and error correction model (ECM). Using this model to avoid a spurious regressioan in non stationary data of time series. The statistical test suggest that inflation has positive and significant influence on the nominal interest rate (SBI). Howaver, this influence just on the short run period. Interesting finding in this research is that in short-run nominal interest rate (SBI) was it influenced by actual inflation rate at pertinent period with positive influence, the phenomenon as according to The Fisher Hypothesis. Thus, a weak version off Fisher effect and was found in Indonesia during the period.Keywords: Fisher effect, inflation, dynamic model